Iatrogenic Perforation of Stomach - A Case Report - Nithin, M.D.; Marigoudar, R.M.; Rani, S.; Johnson, L.R. (Kathmandu University Medical Journal, 2017)
Gastric lavage is a routine procedure done in many cases of poisoning and it has been advocated by many as a lifesaving procedure. There may be some instances, where it might be unnecessary, ineffective or even detrimental to life. A 35 year old man walked into a casualty, 2 hours after having ingested 15 benzodiazepine tablets. Lavage was done by an unqualified person using Ewald’s tube, leading to iatrogenic perforation. The unwarranted use of the procedure proved to be fatal.